Structure-Activity Relationships of 3,3′-Phenylmethylene-bis-4-hydroxycoumarins: Selective and Potent Inhibitors of Gram-Positive Bacteria - Kanokporn Petnapapun; Warinthorn Chavasiri; Pornthep Sompornpisut (The Scientific World Journal)
Dicoumarols and coumarin derivatives have shown a variety of pharmaceutical activities and have been found to be potent inhibitor for the NAD(P)H-dependent flavoproteins. In this report, dicoumarol and its derivatives containing the substituted benzene ring at the methylenebis position were synthesized and evaluated for their antibacterial activity against gram-positive bacteria: Staphylococcus aureus and Bacillus subtilis, and gram-negative bacteria: Escherichia coli and Klebsiella sp. The results showed that the synthesized dicoumarols affect cell growth but are selective against gram-positive over gram-negative bacterial cells. However, for most derivatives, the substitution of steric bulky benzene group on the methylenebis position appears to decrease in the efficacy of antibacterial effect. This finding is roughly described by the predicted poorer docked structure of the derivatives to a homology model of S. aureus flavoprotein. 3D-QSAR study highlighted structural features around the substituted benzene ring of dicoumarols as the antibacterial activity. CoMFA and CoMSIA contour maps support the idea that steric repulsion at the para position could diminish the antibacterial activity. The results of this study provide a better understanding of the molecular basis for the antibacterial activity of dicoumarols.